Effect of submerged macrophytes on the structure of lake ecosystem and trophic relationships among fishes - Vejříková, Ivana (Jihočeská univerzita, 2019)
This Ph.D. Thesis is focused on the effect of submerged vegetation on the structure of lake ecosystem and trophic relationships among fishes. Succession of submerged vegetation is a dynamic process and the vegetation community may change dramatically even during a year. Many environmental factors have impact on the succession of submerged vegetation and consequently the presence of the vegetation has substantial impact on the aquatic ecosystem. Nutrient level (mainly nitrogen and phosphorus) plays a key role in the succession of freshwater ecosystems. Further, herbivory significantly influences species composition and biomass of macrophytes and macroalgae. Herbivory of fish is a foraging strategy that is dependent on temperature. Foraging preferences of fish may suppress the palatable species. The rate of herbivory affects plant growth patterns and thus inpalatable species may be advantaged in the competition among plants. In aquatic ecosystems, herbivory is often performed by omnivorous species. The diet preferences of omnivorous fish differ among aquatic ecosystems and submerged vegetation can shape their trophic niches substantially.
Effect of submerged macrophytes on the structure of lake ecosystem and trophic relationships among fishes
Keywords: competition; herbivory; macroalgae; stable isotope analysis; submerged vegetation; succession; trophic niche; competition; herbivory; macroalgae; stable isotope analysis; submerged vegetation; succession; trophic niche